2019
DOI: 10.3389/fonc.2019.00193
|View full text |Cite
|
Sign up to set email alerts
|

The C Allele of ATM rs11212617 Associates With Higher Pathological Complete Remission Rate in Breast Cancer Patients Treated With Neoadjuvant Metformin

Abstract: Background: The minor allele ( C ) of the single-nucleotide polymorphism (SNP) rs11212617 , located near the ataxia telangiectasia mutated ( ATM ) gene, has been associated with an increased likelihood of treatment success with metformin in type 2 diabetes. We herein investigated whether the same SNP would predict clinical response to neoadjuvant metformin in women with early breast cancer (BC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Table 1 indicates the characteristics of the included studies. The selected studies were performed in Italy [ 10 , 19 ], USA [ 20 , 21 ], Great Britain [ 22 , 23 ], Canada [ 13 , 24 ], and Spain [ 25 ]. The sample size was 1047 participants in metformin treatment and control groups, and their age ranged from 42 to 77 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 indicates the characteristics of the included studies. The selected studies were performed in Italy [ 10 , 19 ], USA [ 20 , 21 ], Great Britain [ 22 , 23 ], Canada [ 13 , 24 ], and Spain [ 25 ]. The sample size was 1047 participants in metformin treatment and control groups, and their age ranged from 42 to 77 years.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies assessed the impact of metformin compared to placebo prescribed to breast cancer, and two studies evaluated the impact of metformin in a patient with endometrial cancer. Eight studies indicated the effect of metformin on the insulin levels [ 10 , 13 , 20 , 21 , 22 , 23 , 24 , 25 ], six studies on FBS [ 10 , 20 , 21 , 23 , 24 , 25 ], five on HOMA-IR [ 19 , 20 , 23 , 24 , 25 ], eight on BMI [ 10 , 13 , 19 , 20 , 21 , 22 , 23 , 24 ], and seven on Ki-67 [ 10 , 13 , 19 , 20 , 22 , 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the ever-growing number of individual clinical trials (>300) investigating metformin in the treatment of various types of cancer has highlighted a need for more rigorous planning to focus on potential predictive biomarkers [65]. Along this line, we have recently proposed that the minor allele (C) of the single-nucleotide polymorphism (SNP) rs11212617, located near the ataxia telangiectasia mutated gene, might warrant consideration as a predictive clinical biomarker to inform the personalized used of metformin in breast cancer patients [66]. In contrast to predictive biomarkers, which attempt to a priori predict the likelihood to respond to a particular treatment from the properties of the tumor, pharmacodynamic biomarkers provide a post-treatment measure of whether a given drug has reached its target, exerted a pharmacological response, and the degree of such response [67].…”
Section: Discussionmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNP) are one of the most common human genetic variations, accounting for more than 90% of all known polymorphisms, and hundreds have been found to be associated with T2DM. 4 , 5 However, reported studies only explain some of the causes of T2DM, and further investigation is needed to fully understand the relationship between SNPs and T2DM.…”
Section: Introductionmentioning
confidence: 99%